Analysis of Different Key Behavioral Patterns to Score in Elite Taekwondoists According to the Weight Category and Gender - Menescardi, Cristina; Falcó, Coral; Hernández-Mendo, Antonio; Morales-Sánchez, Verónica (Frontiers in Psychology, 2021)
Traditionally, research in taekwondo has focused on athletes' overall performance considering the entire sample of the tournament or analyzed selected bouts while ignoring behavioral differences of athletes according to their gender and weight category. Thus, the aim of this study was to analyze the behavioral patterns used to score points in the London Olympic Games according to gender and weight category (fin [FW], feather [FTW], light [LW], and heavy [HW]) of the athletes. A total of 24,940 actions were analyzed by using observational methodology, a mixed method methodology where lag sequential and polar coordinate analysis were applied. Different patterns could be seen in the actions performed prior to score between the weight categories for both genders. To score one point, females FW performed dodges, LW used indirect attacks and HW used direct attacks, posterior counterattacks, dodges and blocks. After scoring one-point, female athletes used a variety of actions, defensives like dodges (FW/LW) and blocks (LW), and offensives like simultaneous counterattacks (FW, FTW, LW) and posterior (FTW) as well as direct (FTW, HW) and indirect (FW) attacks. No patterns were found in males when scoring one-point, only LW competitors performed a sequence characterized by the performance of dodges followed by indirect attacks prior scoring while simultaneous counterattacks occurred after score one point. To score two points, similar patterns were found for all weight groups among female competitors. Females performed openings prior to scoring (LW/HW), while anticipatory (FW/FTW) and posterior counterattacks (LW) occurred after scoring, followed by cuts (FW), direct attacks (LW) and openings (HW). In males, FTW and HW used counterattacks prior to scoring (posterior and simultaneous), while FTW and LW also used counterattacks after scoring (anticipatory and simultaneous). Prior to scoring three points different patterns were found according to the weight category, while FW females used cuts and openings, LW used dodges and posterior counterattacks. After scoring three points, FW continued to use cuts, openings and posterior counterattacks while FTW used indirect attacks and HW used simultaneous counterattacks. On the contrary, similar behavior was found in males.